The Casual Sky Observer's Guide Stargazing with Binoculars and Small Telescopes - De Laet, Rony.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Here is an invaluable guide for those stargazers who are just starting out on their fascinating journey. Don't know what sights to look for? How to locate them? What seasons are best for viewing what stars? All that and more is included in these pages. Plus lots of tips for what equipment to use and good observing techniques. Take this with you to your viewing site, along with your equipment, and you're ready to begin. The universe is there for your viewing pleasure. Enjoy!
Preface -- Chapter 1: Navigating the Sea of Stars -- Chapter 2: Welcome to the Milky Way -- Chapter 3: January -- Chapter 4: February -- Chapter 5: March -- Chapter 6: April -- Chapter 7: May -- Chapter 8: June -- Chapter 9: July -- Chapter 10: August -- Chapter 11: September -- Chapter 12: October -- Chapter 13: November -- Chapter 14: December -- Chapter 15: Taking it further -- Glossary -- Index.
Keywords: Physics; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy